Monitoring the Italian transposition of the EU regulation concerning renewable energy communities and the relevant policies for battery storage - De Juan-Vela, Pablo; Alic, Asja; Trovato, Vincenzo (Journal of cleaner production, 2023)
This paper deals with the transposition of the European Union (EU) Directive concerning Renewable Energy Communities (RECs) into the Italian legislation. The methodology aims at identifying those national provisions which do not comply with the EU legislation. Consequently, long and onerous infringement procedures may ultimately limit the development of RECs. Moreover, the proposed methodology quantifies the economic value of national policies concerning the participation of storage assets in RECs. Three policy options are compared against the case without flexible assets. To do so, ad-hoc mixed-integer linear programming optimization problems are developed. The assessment is based on the formulation of three key performance indicators, concerning the revenues and costs of the REC. The main data sources in the work are the actual Italian Wholesale Market prices and the price incentives introduced by relevant Italian authorities to support the operation of the RECs. Results indicate an incorrect transposition of the fundamental rights of the EU law. These concern a significant alteration of the membership criteria for prospective RECs and the introduction of external third-parties, which may bypass fundamental requirements set out in the EU law. Numerical results call for a profound revision of the policy options for battery storage in RECs since the envisaged configurations introduce structural limits to the REC's revenues This work can support researchers and policy makers at both national and EU-level in developing policy options and techno-economic measures that foster the development of new RECs. •The Italian transposition of the EU Directive for Renewable Energy Community is not fully complete.•The Italian transposition of the RED-II have indicated non-negligible criticalities.•The main criticalities deal with the membership criteria and the presence of third-parties, which bypass EU requirements.•The policy options for battery storage in renewable energy communities in Italy limit the contribution of flexible assets.•A clearer definition of environmental, economic or social community benefits is crucial to success of the communities.